Incorporating the effect of urbanization in measuring climate adaptive capacity. (November 2017) - Chu, Andrea; Lin, Ying-Chen; Chiueh, Pei-Te
Graphical abstract: Highlights: The effect of urbanization and land use change on adaptive capacity is understudied. An adaptive capacity indicator system based on land use change is established. The index is applied to two case studies, Tamsui, Taiwan and West Palm Beach, USA. Benefits of urbanization increase, peak, and decline as land cover is transformed. Urbanization benefits in Tamsui have peaked, while West Palm Beach may not have yet. Abstract: Measuring the ability of a community to face climatic changes, or its adaptive capacity, is necessary in order to plan and guide development as the global climate continues to warm. One factor that has not been thoroughly addressed by previous attempts at measuring adaptive capacity is urbanization. This study looks to measure adaptive capacity in relation to urbanization, as many areas of the world are undergoing this rapid transition. An indicator system was created with land-use sensitive measures and applied to three different land use projection scenarios (A, BAU, and B − high, medium, and low growth, respectively) to 2030 and 2050 for two case study areas, Tamsui, Taiwan and West Palm Beach, USA. In Tamsui, the adaptive capacity decreased in all scenarios, but most dramatically for the high growth scenario. The low growth scenario decreased more slowly through each time slice. For West Palm Beach, the high growth scenario had the highest score in 2030, but declined in 2050. The medium growth Scenario BAU, also had a higher adaptive capacity score in 2030 than in 2050. The low growth Scenario B had a score that improved less dramatically but continued to rise through 2050. Scenario A would be ideal for short term gains, but its benefits would plateau in the long term. Scenario B, with conservation measures and more restricted growth would be the most ideal alternative. This study shows that urbanization has short term socioeconomic gains, but long term environmental consequences. The results also successfully incorporates the effect of land use change into an adaptive capacity indicator system, and can be applied in other localities expecting significant increases in urbanization.